Pengaruh Variasi pH Saliva terhadap Kekerasan Resin Komposit Bulk-Fill - Nasya K. Mahandini; Donna Hermawati; Oedijani Santoso; Nadia Hardini (e-GiGi, 2024)
Abstract: Composite resin is the most widely used restorative material in dentistry. The filling that has been applied will always be in contact with saliva in the oral cavity. This study aimed to determine the effect of salivary pH variations on the hardness of bulk-fill composite resin. This was an experimental study with a post-test only with a control group design. Samples consisted of 28 bulk-fill composite resin samples with 8 mm diameter and 4 mm thickness. Samples were divided into four groups, as follows: group I, soaked in saliva with a pH of 5.3; group II, soaked in saliva with a pH of 6.6; group III, soaked in saliva with a pH of 7.8; and a control group, not treated. The hardness of the samples was measured using Vickers hardness tester. Data were analyzed using the Analysis of Variance (ANOVA) test. The results showed that the mean and standard deviation (SD) hardness values of the bulk-fill composite resin in the control group, groups I, II and II were 63.933 ±4.721 VHN, 63.233±3.518 VHN, 64.683±7.600 VHN, and 69.267±12.545 VHN respectively. These results indicated that there was a decrease in hardness in group I and an increase in hardness in groups II and III. The ANOVA test showed that there was no significant difference in all groups with a p-value of 0.474 (p>0.05). In conclusion, variations in salivary pH do not significantly affect the hardness of bulk-fill composite resin. Keywords: salivary pH; bulk-fill composite resin; hardness of resin   Abstrak: Resin komposit merupakan bahan restorasi dibidang kedokteran gigi yang paling banyak digunakan. Tumpatan yang telah diaplikasikan akan selalu berkontak dengan saliva yang terdapat di rongga mulut. Tujuan penelitian ini ialah untuk mengetahui pengaruh variasi pH saliva terhadap kekerasan resin komposit bulk-fill. Jenis penelitian ialah eksperimental dengan post-test only with control group design. Sampel penelitian terdiri dari 28 sampel resin komposit bulk-fill dengan diameter 8 mm dan tinggi 4 mm, yang dibagi menjadi empat kelompok, yaitu: kelompok I direndam pada saliva dengan pH 5,3; kelompok II direndam pada saliva dengan pH 6,6; kelompok III direndam pada saliva dengan pH 7,8; dan kelompok kontrol tidak dilakukan perendaman. Kekerasan sampel diukur menggunakan Vickers hardness tester. Data dianalisis menggunakan uji Analysis of Variance (ANOVA). Hasil penelitian mendapatkan nilai rerata dan standar deviasi (SD) kekerasan resin komposit bulk-fill pada kelompok kontrol, kelompok I, II dan II ialah 63,933±4,721 VHN, 63,233±3,518 VHN, 64,683±7,600 VHN, dan 69,267±12,545 VHN secara berurut. Hasil tersebut menunjukkan bahwa terjadi penurunan kekerasan pada kelompok I dan terjadi peningkatan kekerasan pada kelompok II dan III. Uji ANOVA menunjukkan bahwa tidak terdapat perbedaan bermakna pada semua kelompok dengan nilai p 0,474 (p>0,05). Simpulan penelitian ini ialah variasi pH saliva tidak berpengaruh secara bermakna terhadap kekerasan resin komposit bulk-fill. Kata kunci: pH saliva; resin komposit bulk-fill; kekerasan resin